THE EFFECT OF PERCEIVED VALUE, CUSTOMER SATISFACTION AND TRUST ON CUSTOMER LOYALTY AT THE DM CLINIC IN EAST JAKARTA - Florencia Vanya Vaniara; Rudy Pramono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The increasing number of clinics in big cities creates intense competition. In order to maintain market share, clinics are required to pay attention to customer’s perceived value, customer satisfaction, trust and customer loyalty maintenance. The purpose of this study was to analyze the effect of perceived value, customer satisfaction, and trust on customer loyalty; the effect of perceived value on customer satisfaction; and the effect of customer satisfaction on trust at DM Clinic, East Jakarta. This study involved 150 outpatients who had received health services at DM Clinic. Questionnaires were distributed using Google Form application to collect data based on convenience sampling, the questionnaire used a Likert scale with a value of 1 – 5. All descriptive analysis used SPSS and data analysis used PLS-SEM method. The results of this study stated that there was a positive effect of perceived value on customer loyalty (p = 0.065), perceived value on customer satisfaction (p = 0.05), customer satisfaction on customer loyalty (p = 0.021), customer satisfaction on trust (p = 0,39), trust towards customer loyalty (p = 0.119). This research can be used as input for clinic administrators to provide better service to customers to increase customer loyalty to DM Clinic. This research also has recommendations for further research.